The Analysis of Tree Species Distribution Information Extraction and Landscape Pattern Based on Remote Sensing Images - Zeng, Yi; Wang, Shuang; Luan, Jiaping; Yu, Min (Frontiers in Environmental Science, 2017)
The forest ecosystem is the largest land vegetation type, which plays the role of unreplacement with its unique value. And in the landscape scale, the research on forest landscape pattern has become the current hot spot, wherein the study of forest canopy structure is very important. They determines the process and the strength of forests energy flow, which influences the adjustments of ecosystem for climate and species diversity to some extent. The extraction of influencing factors of canopy structure and the analysis of the vegetation distribution pattern are especially important. To solve the problems, remote sensing technology, which is superior to other technical means because of its fine timeliness and large-scale monitoring, is applied to the study. Taking Lingkong Mountain as the study area, the paper uses the remote sensing image to analyze the forest distribution pattern and obtains the spatial characteristics of canopy structure distribution, and DEM data are as the basic data to extract the influencing factors of canopy structure. In this paper, pattern of trees distribution is further analyzed by using terrain parameters, spatial analysis tools and surface processes quantitative simulation. The Hydrological Analysis tool is used to build distributed hydrological model, and corresponding algorithm is applied to determine surface water flow path, rivers network and basin boundary. Results show that forest vegetation distribution of dominant tree species present plaque on the landscape scale and their distribution have spatial heterogeneity which is related to terrain factors closely. After the overlay analysis of aspect, slope and forest distribution pattern respectively, the most suitable area for stand growth and the better living condition are obtained.